2002
DOI: 10.1177/001440290206800202
|View full text |Cite
|
Sign up to set email alerts
|

Peer Training to Facilitate Social Interaction for Elementary Students with Autism and Their Peers

Abstract: There is increasing evidence that peer-mediated interventions for students with autism are effective in increasing participation in natural settings. Still unknown are the contributions peers make to the generalization of social behaviors. Results from two investigations of this issue are reported. In Study 1, social interaction with peers increased during interventions compared to controls; however, students in cooperative learning control groups showed higher levels of generalization than those in social gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
91
0
12

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 17 publications
9
91
0
12
Order By: Relevance
“…As clinicians search the literature to find effective strategies to employ in their day to day work with clients, they find little solace in the overwhelming number of articles and the variety of training procedures. The research supports the use of each procedure, yet only segmented pieces of intraverbal repertoires are established (Albertson & Billingsley, 1998;Albrecht, 1981;Bell, et al, 1991;Berens, et al, 2003;Braam & Poling, 1983;Chiesa & Robertson, 2000;Killu, et al, 2001;Lovitt, et al, 1985;Luciano, 1986;Miguel, et al, 2005;Ritesman, et al, 1996;Spaulding, et al, 1995;Sweeney, et al, 2001;Tennenbaum & Wolking, 1989;Watkins, et al, 1989) generally with contrived controlling variables (Braam & Poling, 1983;Hunt, et al, 1988;Kamps, et al, 1994;Kamps, et al, 2002;Krantz, et al, 1989) and contrived reinforcement contingencies (Braam & Poling, 1983;Kamps, et al, 1994;Kamps, et al, 2002;Krantz, et al, 1989;Luciano, 1986;Watkins, et al, 1989). Clinicians seek to teach the intraverbal repertoire in its entirety and to establish this repertoire under naturally occurring stimulus control and reinforcement contingencies.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…As clinicians search the literature to find effective strategies to employ in their day to day work with clients, they find little solace in the overwhelming number of articles and the variety of training procedures. The research supports the use of each procedure, yet only segmented pieces of intraverbal repertoires are established (Albertson & Billingsley, 1998;Albrecht, 1981;Bell, et al, 1991;Berens, et al, 2003;Braam & Poling, 1983;Chiesa & Robertson, 2000;Killu, et al, 2001;Lovitt, et al, 1985;Luciano, 1986;Miguel, et al, 2005;Ritesman, et al, 1996;Spaulding, et al, 1995;Sweeney, et al, 2001;Tennenbaum & Wolking, 1989;Watkins, et al, 1989) generally with contrived controlling variables (Braam & Poling, 1983;Hunt, et al, 1988;Kamps, et al, 1994;Kamps, et al, 2002;Krantz, et al, 1989) and contrived reinforcement contingencies (Braam & Poling, 1983;Kamps, et al, 1994;Kamps, et al, 2002;Krantz, et al, 1989;Luciano, 1986;Watkins, et al, 1989). Clinicians seek to teach the intraverbal repertoire in its entirety and to establish this repertoire under naturally occurring stimulus control and reinforcement contingencies.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Krantz, et al (1989) indicated that skills were generalized across settings but settings differed only on one variable -room color. In addition, adults often maintained some stimulus control over responding (Kamps, et al, 1994;Kamps, et al, 2002;Krantz, et al, 1989). Skills that did generalize across conditions did not maintain at the same rates when new peers were introduced.…”
Section: Intraverbal Behaviormentioning
confidence: 97%
See 3 more Smart Citations